2019
DOI: 10.21831/lt.v6i2.10625
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of using multiple intelligence activities in listening comprehension and improving students' interest

Abstract: This study aims to find out (1) the effectiveness difference between the use of multiple intelligence activities and the conventional activities in listening comprehension, and in the students’ interest in learning English. This study used the quantitative method. The study design was quasi- experimental with the pre-test and the post-test group design. The experimental class used 5 categories of multiple intelligences namely; linguistic intelligence, logical/mathematical intelligence, visual intelligence, mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The Effect of a Proposed Instructional Program… poems and songs, doing "a running dictation", and evaluating each other in oral performance. These results are congruent with those of Alilateh & Widyantoro (2019) which concluded that EFL students got high grades in listening tests when they are fully involved in MI activities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The Effect of a Proposed Instructional Program… poems and songs, doing "a running dictation", and evaluating each other in oral performance. These results are congruent with those of Alilateh & Widyantoro (2019) which concluded that EFL students got high grades in listening tests when they are fully involved in MI activities.…”
Section: Discussionsupporting
confidence: 89%
“…This study emanates from the recommendations of some studies which refer to the importance of investigating further studies on the inclusion of MI in English language teaching. For example, the findings of international studies (Alilateh & Widyantoro (2019), Estaji & Nafisi (2014), Kırkgöz (2010) and Taase (2012) hold the implication that curriculum designers should consider the importance of including all intelligence sorts in designing English language textbooks. On the other hand, the researchers, as EFL instructors for more than ten years, have realized that some EFL ninth grade students are unable to use English communicatively.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In fact, IQ has been considered as the only indicator of a person's intelligence, whereas the IQ test only measures intelligence which includes language intelligence and mathematical logic. Real intelligence is more than just linguistic and logical intelligence (Alilateh & Widyantoro, 2019). Eight intelligence according to dr. Howard Gardner are linguistic, logicmathematic, visual spatial, musical, kinestetic, interpersonal, intrapersonal, and naturalist (Kurniawati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the shadowing technique is not limited to simultaneous interpretation, which allows even beginners to benefit from it in mastering listening skills, i.e., understanding information communicated through speech signals (Junipisa & Aristana, 2021), the mastery and efficiency of which is vital. These skills become even more important in foreign language classes since listening as an act is a basic skill in studying any foreign language (Alilateh & Widyantoro, 2019).…”
mentioning
confidence: 99%